Measuring sharenting behavior: Validity and reliability of the Turkish version of the sharenting evaluation scale (Annals of Medical Research, 2023)
Aim: Sharenting, the act of parents sharing content related to their children on social media, has become a prevalent practice in today's digital age. However, concerns have been raised about the potential privacy violations and risks that this behavior may expose children to. This study aimed to investigate sharenting behaviors among Turkish parents and validate the Turkish version of the Sharenting Evaluation Scale (SES).Materials and Methods: Following World Health Organization guidelines, the original SES was translated into Turkish. The scale's content validity was evaluated by experts before being administered to 276 Turkish parents.Results: The overall reliability of the scale was determined to be 0.855, which indicates its strong reliability. To further enhance the scale's reliability, the tenth item was removed after examining item-total statistics, resulting in an improved Cronbach's alpha of 0.87 for the total scale. Subscale reliability was also satisfactory, with values of 0.92 for implications, 0.64 for social behavior, and 0.68 for self-control. Confirmatory Factor Analysis (CFA) was employed to assess the construct validity of the scale. The chi-square test indicated a significant fit (p
Keywords: Children; Privacy; Scale; Sharenting; Social media; Turkish